Cognitive Orientation to Daily Occupational Performance Approach in Iranian Elderly Without Cognitive Impairment: A Single-Subject Study - Elaheh Ebrahimi; Mehrdad Saeidi Borujeni; Mohsen Vahedi; Nazila Akbarfahimi; Seyed Ali Hosseini (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: The elderly population in Iran is growing. Aging is a natural phenomenon that causes changes in brain structures, including the frontal lobe and its connections, which are responsible for the brain's executive functions. These structural changes lead to problems in cognitive and physical functioning. Older people face problems such as decreased performance in daily activities of life and participation in social activities. In cognitive orientation to the daily occupational performance approach, the participants learn to improve their motor performance using cognitive strategies. The effectiveness of this approach has been reported in stroke, Traumatic Brain Injury (TBI), and some childhood disorders. This study aimed to investigate this approach's feasibility and its effect on the Iranian elderly without cognitive problems. Materials & Methods: A single-subject study A-B design with follow-up was conducted. The participants were two older adults referred to Ramsar Health Center, Ramsar City, Iran. Before the intervention, to examine the participants' cognitive status, we used Digit Span Forward to measure attention and Digit Span Backwards and Digit Symbol to measure working memory. The participants' executive function was also assessed by the Wisconsin Card Sorting Test and Independence in Activity of Daily Living (ADL) with Functional Independent Measure (FIM). Each participant selected three functional goals by Canadian Occupational Performance Measure (COPM) for the focus of the Cognitive Orientation to daily Occupational Performance (CO-OP) intervention. After two weeks of evaluating participants' performance on selected goals using the Performance Quality Rating Scale (PQRS) to determine baseline performance, the intervention period began. During this period, a total of 8 to 10 sessions were held for each participant. In these sessions, the participants were first taught global problem-solving strategies (Goal, Plan, Do, Check), and then they were introduced to domain-specific strategies and their importance in executing activities. Afterward, through guided discovery during implementation, they were directed to use these strategies in their execution by guided discovery. During this period, the participant's performance on the selected goals was assessed five times by the PQRS. At the end of the intervention, to evaluate the long-term impact of the intervention, the participant's performance on the selected goals was re-evaluated by the PQRS three times. Results: The PQRS results showed that the performance of the first participant in each of the three selected activities improved. The results of the PQRS for the second participant showed a significant improvement in performance on the two selected goals. However, one of the selected goals did not show a significant change, which may be related to this goal's nature. Participants' net scores in FIM and COPM showed improved performance and satisfaction on selective goals, and performance independence remained constant. Conclusion: The CO-OP approach is feasible in the Iranian elderly population, and the preliminary results indicate the positive impact of this approach on improving the performance in the trained goals. However, given the study limitations in interpreting the results, it is recommended that future studies with a larger sample size be conducted to evaluate the effectiveness and efficacy of this approach. It is also recommended to use alternative tools instead of PQRS to evaluate the results, given the different cultural contexts.